1982
DOI: 10.1046/j..1982.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective survey of students' views on a family therapy training programme

Abstract: This paper describes the development of the training programme offered at the Family Institute in Cardiff and presents the results of a retrospective survey reflecting the ‘consumers’ views of the programme. Questionnaires were sent to all students who had trained at the Institute between 1972 and 1977, to elicit information about their views of the placement, as well as their post‐qualifying experience, activities and interest in family therapy. A briefer preliminary report has been published earlier (Dowling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the growing literature on family therapy training the perspective of the trainee has rarely been investigated. An extensive literature search identified only two studies reporting on students' views of their family therapy training (Dowling et al ., 1982; Green and Kirby‐Turner, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the growing literature on family therapy training the perspective of the trainee has rarely been investigated. An extensive literature search identified only two studies reporting on students' views of their family therapy training (Dowling et al ., 1982; Green and Kirby‐Turner, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Dowling et al . (1982) described the development of a family therapy programme for social work students on placement and presented the results of a retrospective questionnaire survey of these students' views about the programme.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been studies that explore the experience of self of the therapist (Aponte et al, 2009), little research has investigated the experience of students or trainees learning couple and family therapy. For example, Nel (2006) did an extensive literature review of qualitative research about students' views of family therapy training and identified only two studies (Dowling, Cade, Breunlin, Frude, & Seligman, 1982;Green and Kirby-Turner, 1990). Other reviews of research that explores the training of couple and family therapists have been few and repeat the refrain of the limitation of the research in this area (e.g.…”
mentioning
confidence: 99%
“…Birleson and Sills, 1981); surveys of client families and family therapy trainees (e.g. Dowling et al, 1982;Frude and Dowling, 1980); reports on family scoring methods either borrowed from other contexts developed and carefully standardized (e.g. Kinston et al, 1979).…”
Section: Introductionmentioning
confidence: 99%